2021
DOI: 10.1099/jmm.0.001343
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and clinical isolates of Herbaspirillum induce pulmonary infection in mice and its secretome is cytotoxic to human lung cells

Abstract: Introduction. In recent years, the Herbaspirillum genus has emerged as a pathogen in healthcare-related infections and has became stablished as an opportunistic pathogen. Hypothesis/Gap Statement. Little is known about the pathogenesis induced by Herbaspirillum genus. Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…huttiense AU11883 and H. frisingense AU14559 showed that the clinical strains can adhere to lung Calu-3 cells. Furthermore, the treatment of Calu-3 cells with the strain AU14559 secretome led to drastic changes in cell morphology [ 65 ]. The rhizosphere is a nutrient-rich environment due to the exudates released by the plants, and this generates great competition between the bacteria present in this environment and thus acts as a selection factor for cells with more efficient nutrient and mineral uptake mechanisms; this is a common feature among human pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…huttiense AU11883 and H. frisingense AU14559 showed that the clinical strains can adhere to lung Calu-3 cells. Furthermore, the treatment of Calu-3 cells with the strain AU14559 secretome led to drastic changes in cell morphology [ 65 ]. The rhizosphere is a nutrient-rich environment due to the exudates released by the plants, and this generates great competition between the bacteria present in this environment and thus acts as a selection factor for cells with more efficient nutrient and mineral uptake mechanisms; this is a common feature among human pathogens.…”
Section: Discussionmentioning
confidence: 99%